A model of teacher enthusiasm, teacher self-efficacy, grit, and teacher well-being among English as a foreign language teachers - Shao, Guohua (Frontiers in Psychology, 2023)
This study aimed to investigate the relationship among teacher enthusiasm and teacher self-efficacy, grit, and teacher psychological well-being among Chinese English as a foreign language (EFL) teachers. A sample of 553 Chinese EFL teachers completed self-report measures of teacher enthusiasm, teacher self-efficacy, grit, and teacher psychological well-being. Confirmatory factor analysis was used to confirm the validity of the scales, and structural equation modeling was used to test the hypothesized model. The results indicated that teacher self-efficacy and grit were positively associated with teacher psychological well-being, providing support for the importance of these teacher characteristics in promoting teacher well-being. Furthermore, teacher enthusiasm was found to have an indirect effect on teacher psychological well-being through the mediation of teacher grit, providing evidence for the importance of teacher motivation and engagement in promoting teacher well-being. The partial mediation model was found to be the best fitting model. These findings have important implications for the development of interventions and programs aimed at promoting teacher well-being in the context of EFL teaching.